PENGARUH KREDIT TERHADAP PENDAPATAN BUNGA PADA PT BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, Tbk. - Eva, Eva Siti Nurhayati; Euis Hernawati (JEBS (Journal of Economic and Business Student), 2023)
The purpose of this study was to determine the effect of credit on interest income at PT Bank Pembangunan Daerah Jawa Barat and Banten, Tbk. The method used in this research is quantitative with product moment correlation analysis, determination analysis and simple linear regression analysis, data collection techniques in this study are observation, documentation, literature study and internet browsing. The results showed product moment correlation analysis that the value of the relationship between credit and interest income was Sig.0.043 <0.05, meaning that there was a significant relationship. The results of determination show that the effect of credit on interest income is 79.3%. The results of simple linear regression analysis show that credit to interest income has a very strong and positive influence, which means that there is a direct and significant relationship. There are obstacles that occur, namely bad credit. In dealing with these obstacles, the efforts made are to overcome bad credit by changing the payment schedule including the number of installments, as well as better services provided and digital products provided to facilitate customer transactions such as DigiCash and DigiMobile.